Self-Development Needs of Teachers and Personnel Under the Division of Religious and Cultural Education Si Sa Ket Provincial Administrative Organization - Prangsri, Napassaraphi; Wongwatkasem, Wiralphat; Romsri, Suwattanapong (Journal for Developing the Social and Community, 2022)
The Study have a purpose To study and compare the self-Development Needs of Teachers and Personnel Under the Division of Religious and Cultural Education Si Sa Ket Provincial Administrative Organization according to the needs of personnel classified by gender, educational level and work experience. The population used in this research were teachers, personnel under the Division of Religious and Cultural Education, Si Sa Ket Provincial Administrative Organization, Academic Year 2020, consisted of 2,154 people, a sample of 326 people. The research instrument was a questionnaire which was a 5-level estimation scale with a reliability of 0.90. The basic statistics used for data analysis were frequency, percentage, mean, standard deviation, and the statistic used to test the hypothesis was t. -test and F-test. research results 1. Self-development needs of teachers and personnel under the Education Division religion and culture local government organization Sisaket Province Overall, at a high level When considering each aspect, it was found that Self-development needs of teachers and personnel At a high level in every item The averages were arranged in descending order, i.e. physical self-development. emotional self-improvement social self-development Intellectual self-development, respectively. 2. Self-development needs of teachers and personnel under the Education Division religion and culture local government organization Sisaket Province according to the needs of personnel, classified by gender, educational, work experience, overall was no difference.